The Functional Grammar of Dance applied to ELAN annotation: meaning beyond the naked eye - Maiorani Arianna; Liu Chun (Journal of World Languages, 2024)
The main purpose of this article is to show how Functional Grammar of Dance (FGD) can be applied to dance discourse analysis to reveal the discursive strategies that underlie choreographies and support movement-based communication. In recent years, studies in Systemic Functional Multimodal Discourse Analysis (SF-MDA) have benefited from the development of several models of analysis, and from the emergence of a new focus on the materiality of semiotic modes. The Functional Grammar of Dance is a recently developed model of analysis that draws on Systemic Functional Linguistics theory and focuses on movement-based communication starting from dance (particularly ballet as a starting point). The Functional Grammar of Dance has been adopted as a central theory in an international collaborative project funded by the AHRC (Arts and Humanities Research Council) in the UK and the DFG (Deutsche Forschungsgemeinschaft, ‘German Research Foundation’) in Germany, The Kinesemiotic Body, where it has been used with the ELAN annotation system. ELAN annotation based on the Functional Grammar of Dance was used for both live-collected data from dance rehearsals and for dance videos and revealed aspects of dance performances that are not necessarily captured by the naked eye. This paper proposes three case studies where we show that our ELAN annotation with the FGD provides an effective and very flexible interface for the grammaticalization of movement-based communication and the study of movement-based discursive strategies.